2006
DOI: 10.1155/asp/2006/52561
|View full text |Cite
|
Sign up to set email alerts
|

Texture Classification Using Sparse Frame-Based Representations

Abstract: A new method for supervised texture classification, denoted by frame texture classification method (FTCM), is proposed. The method is based on a deterministic texture model in which a small image block, taken from a texture region, is modeled as a sparse linear combination of frame elements. FTCM has two phases. In the design phase a frame is trained for each texture class based on given texture example images. The design method is an iterative procedure in which the representation error, given a sparseness co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 34 publications
0
67
0
Order By: Relevance
“…The proposed method is simple compared to prior work because it contains all texture information in one dictionary. This is different from methods based on learning a dictionary for each class like [11,12,15,18]. Employing an approximate nearest neighbor search makes the encoding complexity O(n log n), and having only one dictionary this search can be done very fast even for large dictionaries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed method is simple compared to prior work because it contains all texture information in one dictionary. This is different from methods based on learning a dictionary for each class like [11,12,15,18]. Employing an approximate nearest neighbor search makes the encoding complexity O(n log n), and having only one dictionary this search can be done very fast even for large dictionaries.…”
Section: Discussionmentioning
confidence: 99%
“…Composed textures Our texture segmentation experiments are compared to [11,18] and the results are shown in Table 1. The proposed method performs better than existing methods in more than half of the samples, and follows closely in the rest.…”
Section: Algorithm 3 Image Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…High segmentation performance is obtained by utilizing that the texture class used for learning the dictionary can be reconstructed well whereas other texture classes cannot. Methods focusing on optimal reconstruction have been suggested [26,30], and improved performance has been obtained by also optimizing for discrimination [21,20]. Recently Gao et al [13] suggested to use sparse dictionaries together with an active contour for segmentation.…”
Section: Introductionmentioning
confidence: 99%